2013
DOI: 10.1021/nl401376w
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructed Stem Cell Nanoghosts: A Natural Tumor Targeting Platform

Abstract: The ultimate goal in cancer therapy is achieving selective targeting of cancer cells. We report a novel delivery platform, based on nanoghosts (NGs) produced from the membranes of mesenchymal stem cells (MSCs). Encompassing MSC surface molecules, the MSC-NGs retained MSC-specific in vitro and in vivo tumor targeting capabilities and were cleared from blood-filtering organs. MSC-NGs were found to be biocompatible. Systemic administration of drug loaded MSC-NGs demonstrated 80% inhibition of human prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
192
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(194 citation statements)
references
References 41 publications
2
192
0
Order By: Relevance
“…Rather than using synthetic membranes, several groups recently began exploring strategies to obtain biological membranes from cells and using them to coat NP surface. We refer to these types of NPs (functionalized or made by cell membranes that provide them with cell-like functions) as 'bio-inspired NPs' [153,154] (Figure 8). …”
Section: Evading the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than using synthetic membranes, several groups recently began exploring strategies to obtain biological membranes from cells and using them to coat NP surface. We refer to these types of NPs (functionalized or made by cell membranes that provide them with cell-like functions) as 'bio-inspired NPs' [153,154] (Figure 8). …”
Section: Evading the Immune Systemmentioning
confidence: 99%
“…Hu et al demonstrated that red blood cell molecules were correctly transferred and oriented on the NPs surfaces [159]. Other bio-inspired NPs whose surface is functionalized through the integration of cell membranes, have been developed [153,[156][157]160]. Among these, we used membrane proteins purified from leukocytes [161] to obtain the Leuko-like Vector (i.e., a nanopourous silica NP coated with leukocyte membranes).…”
Section: Evading the Immune Systemmentioning
confidence: 99%
“…[18][19][20] The use of natural cellular membranes to camouflage synthetic polymeric nanoparticles has demonstrated significant potential. [21][22][23][24][25] In this study, the membranes of human cytotoxic T lymphocytes (hCTLs) were chosen to produce cancer-targeting nanoparticles, because of the long blood circulation time and the ability to recruit and localize at tumor sites, of this cell type. 22 Leukocytes have a variety of proteins on their membranes to detect inflammation and diseased tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, exosomes represent interesting natural carriers potentially exploitable for the delivery of RNAi to a variety of cell types and tissues, including cartilage. Among membrane vesicles-based delivery systems, nanoghosts derived from MSCs are currently under investigation [49,50]. Interestingly, nanoghosts exhibit inherent targeting capabilities, versatile loading capacity, and immuno evasiveness, making them highly attractive for the development of novel gene silencing-based strategies.…”
Section: Non-viral Methods Delivering Rnai For Chondrogenesismentioning
confidence: 99%